The Effect of Skills and Experience on The Performance of Small and Medium Enterprises With Innovation as Mediation Variable - Yadewani, Dorris; Wijaya, Reni; Mursalini, Wahyu Indah; Almasdi (School of Business, IPB University (SB-IPB), 2023)
This study examined the mediating effect of innovation on the relationship between skills, experience and performance of SMEs. The population in this study were all SMEs in the culinary sector which were fostered by the Pariaman City Government which accounted for 27 businesses. The sampling technique uses a non-probability approach, namely purposive sampling In order to test hypotheses, this study performs multiple and hierarchical regression analyses. SPSS version 25 is used to process the data. The results of analysis displayed that skills, experience and innovation positively affected the performance of SMEs. In addtion, the variables of skills and experience were found to have positive effect on innovation. Morever, innovation was proven to mediate the relationship between skills, experience and performance of SMEs. Keywords: skills, experience, innovation, performance of SMEs